Mapping the Research Landscape of Brief Cognitive Behavioral Therapy in High School Education: A VOSviewer-Assisted Literature Review (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
Adolescent mental health needs in schools are rising, yet the global research landscape of Brief Cognitive Behavioural Therapy (Brief CBT) in secondary education is underexplored. A bibliometric analysis of 52 Scopus-indexed publications was conducted using VOSviewer to map trends, thematic clusters, and key contributors. Publications increased steadily over the past decade, peaking after 2020. A shift was observed from individual, clinic-based therapy to school-integrated approaches, including classroom sessions, group formats, digital tools, mindfulness strategies, and peer facilitation. Four thematic clusters emerged: adolescent emotional health, preventive strategies, coping skills, and culturally adapted programmes. Research gaps remain in family engagement, teacher-led delivery, and long-term culturally responsive models, especially in Southeast Asia and Sub-Saharan Africa. This study provides a roadmap for advancing Brief CBT in schools, positioning it as a scalable, accessible, and sustainable component of global school-based mental health systems.